Evaluation of Dietary Supplements Containing Viable Bacteria by Cultivation/MALDI-TOF Mass Spectrometry and PCR Identification - Mohar Lorbeg, Petra; Golob, Majda; Kramer, Mateja; Treven, Primož; Bogovič Matijašić, Bojana (Frontiers in Microbiology, 2021)
Insufficient quality of products containing beneficial live bacteria in terms of content and viability of labelled microorganisms is an often reported problem. The aim of this work was to evaluate the quality of dietary supplements containing viable bacteria available in Slovenian pharmacies using plate counting, matrix-assisted laser desorption ionisation time-of-flight mass spectrometry (MALDI-TOF MS) and species- or subspecies-specific PCR with DNA isolated from consortia of viable bacteria, from individual isolates or directly from the products. 12% of the products (3 of 26) contained insufficient numbers of viable bacteria. 83% of the labelled species (111 in total) were confirmed by PCR with DNA from the product, 74% of these were confirmed by PCR with DNA from viable consortium and 65% of these were confirmed by MALDI-TOF MS analysis of colonies. Certain species in multi-strain products were confirmed by PCR with DNA from viable consortia but not by MALDI-TOF MS, suggesting that the number of isolates examined (3 per labelled strain) was too low. With the exception of Lacticaseibacillus casei and closely related species (Lacticaseibacillus rhamnosus, Lacticaseibacillus zeae), PCR and MALDI-TOF identification results agreed for 99% of the isolates examined, although several MALDI-TOF results had lower score values (1.700 - 1.999), indicating species identification was not reliable. The species Lacticaseibacillus zeae, which appeared in 20 matches of the Biotyper analysis, was identified as Lacticaseibacillus rhamnosus by PCR. MALDI-TOF MS analysis was also unsuccessful in detecting Lactobacillus acidophilus La-5 and Bacillus coagulans due to missing peaks and unreliable identification, respectively. Mislabeling was detected by both methods for two putative Lacticaseibacillus casei strains that turned out to belong to the species Lacticaseibacillus paracasei. PCR remains more successful in subspecies-level identification as long as the database of MALDI-TOF MS spectra is not expanded by building in-house databases. The lack of positive PCR results with viable consortia or colonies, but positive PCR results with DNA isolated directly from the products observed in 10% (11/112) of the labelled strains, suggests the presence of non-culturable bacteria in the products. MALDI-TOF MS is a faster and simpler alternative to PCR identification, provided that sufficient number of colonies are examined.